Unexpected sudden intraoperative cardiac arrest during a gynecologic surgery: A case report. (September 2021) - Sisay, Amanuel; Jemal, Sulaiman; Horsa, Bayisa
Abstract: Introduction: Unexpected cardiac arrest during the intraoperative period contributes to higher morbidity and mortality. All patients undergoing surgery and anesthesia have a risk of having a cardiorespiratory event perioperatively. Presentation of case: A 70 years old female (Gravida 7, Para 7) patient having an elective transvaginal hysterectomy under spinal anesthesia. After 1 hour and 25 minute, the patient had sudden intraoperative cardiac arrest noted with loss of carotid pulse, undetectable blood pressure, and chaotic irregular deflection with decrement of amplitude on ECG. Immediate resuscitation was done with chest compression, endotracheal intubation, and epinephrine administration. The patient extubated in the operation room and wean after a day from vasopressor support in the intensive care unit then patient discharged safely after a week. Discussion: Intraoperative cardiac arrest is a very infrequent and unanticipated adverse event following noncardiac surgery. Urgent surgeries, lower American Society of Anesthesiologists (ASA) physical status, and trauma are major contributors to this unwanted event. 4 ''H'' and 4 ''T'' mnemonics are well-known reversible causes of cardiac arrest. Deterioration in hemodynamic status during surgery is an indicator of an upcoming cardiac arrest. Conclusion: Patients with low risk score for perioperative cardiac event might develop a sudden intraoperative cardiac arrest. Preparation for resuscitation at any time of surgery is very important in the management of sudden and unexpected cardiopulmonary arrest during surgery. Highlights: Cardiac arrest during noncardiac surgery is rare. Intraoperative cardiac arrest can happen in a gynecologic surgery. Early CPR initiation improves post-cardiac arrest outcome. All operation room staff are great contributors to the resuscitation of patient went to cardiac arrest.